Diagnostic performance of plasma biomarkers in patients with acute intestinal ischaemia. Issue 3 (8th January 2014) - Matsumoto, S; Sekine, K; Funaoka, H; Yamazaki, M; Shimizu, M; Hayashida, K; Kitano, M
Abstract: Background: The aim of this study was to evaluate the use of intestinal fatty acid binding protein (I-FABP) and traditional biomarkers in the early diagnosis of acute intestinal ischaemia of different causes. Methods: I-FABP, white blood cell (WBC) count, C-reactive protein, base deficit, lactate, lactate dehydrogenase, aspartate aminotransferase, creatine kinase and D-dimer were measured prospectively in consecutive patients suspected of having acute intestinal ischaemia. Biomarker levels were compared in patients with vascular and non-vascular ischaemia. Results: Two hundred and eight patients with a clinical suspicion of acute intestinal ischaemia were enrolled. Vascular intestinal ischaemia was diagnosed in 24 patients (11·5 per cent), non-vascular ischaemia in 62 (29·8 per cent) and non-ischaemic disease in 122 (58·7 per cent). The levels of most biomarkers (except WBC count and creatine kinase) were significantly higher in the vascular ischaemia group than in the other groups ( P < 0·010). However, none of the biomarker levels differed between patients with non-vascular intestinal ischaemia and those with non-ischaemic disease. Receiver operating characteristic (ROC) curve analysis suggested that I-FABP was best at diagnosing vascular intestinal ischaemia (area under the curve 0·88). Conclusion: Serum biomarkers may be useful in the diagnosis of vascular, but not non-vascular, intestinal ischaemia. Among them, I-FABP shows promise for detecting vascular ischaemia. Abstract : Intestinal fatty acid binding protein shows promise